2020
DOI: 10.3389/fimmu.2020.02091
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage TLR4 and PAR2 Signaling: Role in Regulating Vascular Inflammatory Injury and Repair

Abstract: Macrophages play a central role in dictating the tissue response to infection and orchestrating subsequent repair of the damage. In this context, macrophages residing in the lungs continuously sense and discriminate among a wide range of insults to initiate the immune responses important to host-defense. Inflammatory tissue injury also leads to activation of proteases, and thereby the coagulation pathway, to optimize injury and repair post-infection. However, long-lasting inflammatory triggers from macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 184 publications
(232 reference statements)
0
39
0
Order By: Relevance
“…LPS contains lipid A, a non-repeating “core” of oligosaccharide that has the endotoxic properties and is recognized by its Toll Like Receptor 4 (TLR4). It was known that TLR4 is expressed on the cell surface of macrophages and the activation of TLR4 mediates the inflammatory response in lung macrophages [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…LPS contains lipid A, a non-repeating “core” of oligosaccharide that has the endotoxic properties and is recognized by its Toll Like Receptor 4 (TLR4). It was known that TLR4 is expressed on the cell surface of macrophages and the activation of TLR4 mediates the inflammatory response in lung macrophages [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…NRH supplementation induced phosphorylation of p65, a hallmark of NFkB activation, indicating activation of this pathway. The NF-kB pathway is one of the main pathways involved in inflammation and cytokine production in macrophages, and pro-inflammatory stimuli such as LPS are potent activators of this pathway (49). Thus, NRH and LPS might activate similar pro-inflammatory pathways in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the findings from previous studies ( Li X. et al, 2020 ; Yang et al, 2020 ). When TLR4 is activated, it can regulate the expression of various inflammatory mediators and cytokines through transmembrane signaling, and initiate defense and immune regulation ( Rahimifard et al, 2017 ; Rayees et al, 2020 ). Studies have shown that TLR4-mediated inflammatory response plays an important role in heart, lung, liver, and cerebral I/R injury ( Rayees et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…When TLR4 is activated, it can regulate the expression of various inflammatory mediators and cytokines through transmembrane signaling, and initiate defense and immune regulation ( Rahimifard et al, 2017 ; Rayees et al, 2020 ). Studies have shown that TLR4-mediated inflammatory response plays an important role in heart, lung, liver, and cerebral I/R injury ( Rayees et al, 2020 ). After cerebral ischemia, TLR4 recognizes the endogenous substances released from brain tissue such as heat shock protein, fibrinogen, hyaluronic acid, heparan sulfate, etc., and finally activates NF-κB.…”
Section: Discussionmentioning
confidence: 99%